Volume growth and escape rate of symmetric diffusion processes. Issue 3 (2nd April 2016) - Ouyang, Shunxiang
Abstract : We give an upper rate function, in terms of the volume growth of the underlying state space, for the symmetric diffusion process associated with a symmetric, strongly local regular Dirichlet form. It extends the main result of Hsu and Qin [Ann. Probab. 38(4) 2010], where an upper rate function was given for Brownian motion on Riemannian manifold.